Estudo do desempenho fermentivo da levedura kluyveromyces marxianus atcc 36907 com auxílio de modelagem fenomenológica - Tavares, Bruna (2017)
Kluyveromyces marxianus yeast has been arousing importance in the Biotechnology area due to its high metabolic diversity and high degree of polymorphism. Its potentialities have been under study for several applications such as enzymes production of great interest in the food industry such as β-galactosidases, β-glucosidase and polygalactosidase, in the production of aromatic compounds and higher alcohols such as phenyl ethanol, also in biorefineries to produce the second generation ethanol. This yeast has great interest due to bioethanol production and its ability on assimilating different carbohydrates from lignocellulosic biomass as well as its broad spectrum of thermotolerance. Cellulosic ethanol has been presented as a possibility for increasing yield in sugarcane mills and as one of the alternatives to decrease the crisis that affects this sector. Sugarcane biomass, just like all lignocellulosic material, is formed by three main fractions: cellulose, hemicellulose and lignin. The lignocellulosic fiber, after going through pretreatments for separation and break this complex, originates fermentable sugars that can be biotransformed into ethanol. Acid hydrolysis pretreatment is a well-established process, in which monomers are released, and xylose is released from hemicellulose in higher rate, in order to obtain the cellulignin. After biomass delignification, cellulose must be submitted to acid hydrolysis or enzymatic processes to solubilize glucose. Enzymatic hydrolysis and fermentation can occur separately (SHF) or simultaneously (SSF), and this last one has an advantage of performing these two steps in the same reactor. Furthermore, this process requires thermotolerant yeasts able to withstand near to 50 °C, an optimized range for cellulase performance. In addition, another obstacle to produce ethanol is its accumulation in the medium, leading to inhibition by the product during the fermentation process and toxicity for the yeast. K. marxianus yeast has interesting metabolic characteristics that are able of overcoming such difficulties during cellulosic ethanol production. So, it requires more studies, since there is no knowledge about the optimal initial concentrations of substrate for ethanol production by this yeast and on its endurance to the product. Thus, this trial aims at evaluating the fermentative behavior of K. marxianus ATCC 36907 yeast in semi-defined medium with variations in substrate and temperature concentrations using phenomenological modeling, as well as evaluating the effect of ethanol removal on its fermentative activity. In the first step of this trial, fermentations were obtained in a shaking incubator using a semi-defined medium supplemented with peptone, malt extract and yeast extract, with variations in glucose concentrations (50, 120 and 190 g L-1) and temperature (30, 35, 40 and 45 °C). The experimental results were put mathematically together to obtain a theoretical model of the process by the phenomenological modeling with Scilab software. The obtained models represented satisfactorily cell development curves, substrate consumption and ethanol production. The optimization ethanol fermentation process indicated 40 °C as temperature and a substrate concentration of 90 g L-1 to maximize the product concentration, resulting in an average of 22.5 g L-1 ethanol and 0.24 g g-1 yield. During its second step, the fermentations were carried out in triplicates under the optimized conditions in a 1.2-L volume fermenter. Control fermentations were carried out in triplicate without ethanol extraction by vacuum and fed after 36 hours, while the other fermentations, also in triplicate, were carried out under the same conditions, but with the product extraction by vacuum. After the first 36-hour cycle, ethanol concentration was 34.13 g L-1 (YP/S 0.38 g g-1 and QP 0.94 g L-1 h-1), reaching 40.90 g L -1 ethanol (YP/S 0.18 g g-1 and QP 0.43 g L-1 h-1) at the end of the second cycle. A different behavior was observed in the control experiment, in which ethanol production occurred in the first cycle (36.37 g L-1, YP/S 0.4 g g-1 and QP 1.01 g L-1 h-1), whereas in the second cycle, the substrate consumption was 8% and ethanol production was not observed. The phenomenological modeling showed that the experimental data were better represented by the model that took into account the occurrence of a latency phase at ix the beginning of the second cycle and strongly indicated a metabolism inhibition by product accumulation. K. marxianus yeast recovered its fermentative metabolism and produced ethanol again, demonstrating the relevant role of product removal in improving such process.